2004
DOI: 10.2337/diacare.27.8.1866
|View full text |Cite
|
Sign up to set email alerts
|

Improved Plasma Glucose Control, Whole-Body Glucose Utilization, and Lipid Profile on a Low-Glycemic Index Diet in Type 2 Diabetic Men

Abstract: OBJECTIVE -To determine whether a chronic low-glycemic index (LGI) diet, compared with a high-glycemic index (HGI) diet, has beneficial effects on plasma glucose control, lipid metabolism, total fat mass, and insulin resistance in type 2 diabetic patients.RESEARCH DESIGN AND METHODS -Twelve type 2 diabetic men were randomly allocated to two periods of 4 weeks of an LGI or HGI carbohydrate diet separated by a 4-week washout interval, in a crossover design. RESULTS -TheLGI diet induced lower postprandial plasma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

11
170
2
3

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 220 publications
(186 citation statements)
references
References 39 publications
11
170
2
3
Order By: Relevance
“…Our dietary GI and GL values (65 and 147), consistent with those in a previous Japanese study (64 and 150) (Amano et al, 2004), were higher when compared with those in Western countries (49-58 and 81-145) (Salmeron et al, 1997a, b;Toeller et al, 2001;Heilbronn et al, 2002;JimenezCruz et al, 2003;Rizkalla et al, 2004;Scholl et al, 2004;Schulze et al, 2004Schulze et al, , 2005Ma et al, 2005;Sahyoun et al, 2005). This may primarily result from the differences in the major food contributors, whereas dietary GI and GL in Western populations were determined by a variety of foods (potatoes (7-8%), breakfast cereals (4-7%), bread (5%) and rice (5%)) (Liu et al, 2000(Liu et al, , 2002Jonas et al, 2003), the contribution of white rice (GI ¼ 77) was dominant in the present study (46%).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our dietary GI and GL values (65 and 147), consistent with those in a previous Japanese study (64 and 150) (Amano et al, 2004), were higher when compared with those in Western countries (49-58 and 81-145) (Salmeron et al, 1997a, b;Toeller et al, 2001;Heilbronn et al, 2002;JimenezCruz et al, 2003;Rizkalla et al, 2004;Scholl et al, 2004;Schulze et al, 2004Schulze et al, , 2005Ma et al, 2005;Sahyoun et al, 2005). This may primarily result from the differences in the major food contributors, whereas dietary GI and GL in Western populations were determined by a variety of foods (potatoes (7-8%), breakfast cereals (4-7%), bread (5%) and rice (5%)) (Liu et al, 2000(Liu et al, , 2002Jonas et al, 2003), the contribution of white rice (GI ¼ 77) was dominant in the present study (46%).…”
Section: Discussionsupporting
confidence: 90%
“…Several ad libitum trials conducted on nondiabetic subjects have suggested a beneficial effect of low-GI diet on fat mass (Bouche et al, 2002) and body weight (Bouche et al, 2002;Sloth et al, 2004), when compared with high-GI diet, although other trials conducted on subjects with type II diabetes have found no differences in body weight change between high-and low-GI diets (Heilbronn et al, 2002;Jimenez-Cruz et al, 2003;Rizkalla et al, 2004). Additionally, although there has been no association between dietary GI and GL and BMI in some studies (Amano et al, 2004;Liese et al, 2005), other observational studies have shown a positive association between dietary GI, but not dietary GL and BMI Murakami et al, 2006b).…”
Section: Discussionmentioning
confidence: 99%
“…Results were consistent among type II diabetic patients (Jenkins et al, 1988(Jenkins et al, , 2002Gulliford et al, 1989;Wolever et al, 1992;Jarvi et al, 1999;Tsihlias et al, 2000;Heilbronn et al, 2002;Kabir et al, 2002;Brynes et al, 2003;Gilbertson et al, 2003), where low-GI diet improved plasma glucose control and had the added benefit of significantly decreasing cholesterol. Supporting the results from our study, a limited number of clinical trials have demonstrated that low-GI dietary educational interventions delivered by a clinical nutritionist can lead to improved metabolic control in patients with diabetes (Frost et al, 1994;Gilbertson et al, 2001Gilbertson et al, , 2003Rizkalla et al, 2004). These reports are consistent with our findings.…”
Section: Discussionsupporting
confidence: 91%
“…This might suggest an improvement in hepatic insulin sensitivity resulting in a decrease in hepatic glucose output following meals (Thorburn et al, 1993). Whole body glucose utilization has been shown to improve on a low GI diet as assessed by euglycaemic-hyperinsulinaemic clamp (Rizkalla et al, 2004). This is clinically relevant as raised postprandial glycaemia would increase cardiovascular risk even in the normal glucose tolerance range, although this may be confounded by other heart disease risk factors (Coutinho et al, 1999;The DECODE Study Group, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless only the low GI group had an improvement in blood glucose levels supporting Wolever's observation (Wolever, 2003) that the metabolic advantage of a slowly absorbed diet (low GI diet) is greater than its glycaemic impact. Reducing the glycaemic load via reduction in carbohydrate intake increases postprandial free fatty acids (FFAs) possibly via reduced insulin secretion and sensitivity (Wolever and Mehling, 2003) whereas a low GI diet suppresses FFAs (Rizkalla et al, 2004). A high plasma FFA concentration is associated with dyslipidaemia and an increased risk of cardiovascular disease (Carlsson et al, 2000).…”
Section: Discussionmentioning
confidence: 99%